Enforced Freedom: Electric‐Field‐Induced Declustering of Ionic‐Liquid Ions in the Electrical Double Layer. Issue 3 (29th August 2020) - Zhang, Yufan; Ye, Ting; Chen, Ming; Goodwin, Zachary A.H.; Feng, Guang; Huang, Jun; Kornyshev, Alexei A.; Agnese, Yohan Dall'
Abstract : Ions in the bulk of solvent‐free ionic liquids bind into ion pairs and clusters. The competition between the propensity of ions to stay in a bound state, and the reduction of the energy when unbinding in electric field, determines the portion of free ions in the electrical double layer. We present the simplest possible mean‐field theory to study this effect. "Cracking" of ion pairs into free ions in electric field is accompanied by the change of the dielectric response of the ionic liquid. The predictions from the theory are verified and further explored by molecular dynamics simulations. A particular finding of the theory is that the differential capacitance vs potential curve displays a bell shape, despite the low concentration of free charge carriers, because the dielectric response reduces the threshold concentration for the bell‐ to camel‐shape transition. The presented theory does not take into account overscreening and oscillating charge distributions in the electrical double layer. But in spite of the simplicity of the model, its findings demonstrate a clear physical effect: a preference to be a charged monopole rather than a dipole (or higher order multipole) in strong electric field. Abstract : This article presents a simple theory of a physically expected effect of crashing neutral ion clusters in ionic liquids near an electrode, which is the stronger, the higher the electrode polarization.